2022
DOI: 10.3390/ijms23168847
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Analysis of Cathelicidin in Response to Organic Dust Exposure and Related Chronic Lung Illnesses

Abstract: Over two billion people worldwide are exposed to organic dust, which can cause respiratory disorders. The discovery of the cathelicidin peptide provides novel insights into the lung’s response to organic dust; however, its role in the lung’s response to organic dust exposure and chronic lung diseases remains limited. We conducted a scoping review to map the current evidence on the role of cathelicidin LL-37/CRAMP in response to organic dust exposure and related chronic lung diseases: hypersensitivity pneumonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Besides the known protective effects of LL-37 against invading pathogens at the mucosa, several studies have implicated this peptide in COPD ( 289 , 315 , 336 , 337 , 337 , 338 , 338 , 339 , 339 , 340 , 340 , 341 , 341 , 342 , 342 , 343 , 343 , 344 , 344 , 345 , 345 , 346 , 346 351 ). Investigators have demonstrated its association with poor lung function ( 348 , 349 ). In a setting of cigarette-smoke exposure, low levels of LL-37 have been independently associated with lower FEV 1.…”
Section: Antimicrobial Peptides and Lung Damage In Microbiome-immune ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the known protective effects of LL-37 against invading pathogens at the mucosa, several studies have implicated this peptide in COPD ( 289 , 315 , 336 , 337 , 337 , 338 , 338 , 339 , 339 , 340 , 340 , 341 , 341 , 342 , 342 , 343 , 343 , 344 , 344 , 345 , 345 , 346 , 346 351 ). Investigators have demonstrated its association with poor lung function ( 348 , 349 ). In a setting of cigarette-smoke exposure, low levels of LL-37 have been independently associated with lower FEV 1.…”
Section: Antimicrobial Peptides and Lung Damage In Microbiome-immune ...mentioning
confidence: 99%
“…Further investigation into the molecular mechanism of LL-37-mediated-COPD pathogenesis is urgently needed. In the setting of well-established COPD, the profile of LL-37 completely reverses, with several studies reporting elevated levels in COPD compared to healthy controls ( 349 , 354 – 360 ). This peptide is further elevated during acute COPD exacerbations compared to stable disease due to inflammation secondary to bacterial infection ( 296 ), supported by elevated pro-inflammatory cytokines, IL-6, and IL-8 ( 296 ).…”
Section: Antimicrobial Peptides and Lung Damage In Microbiome-immune ...mentioning
confidence: 99%